AUDIOVISUAL CENTER AND AUDIOVISUAL STARTUP - Massarolo, João (2017)
In this work about transmedia centers and audiovisual startup, we intend to problematize and update the notion of APL (Local Productive Arrangement) in the context of the Brazilian audiovisual market, in order to understand the implementation of audiovisual poles as a strategy for developing capable transmedia centers for audiovisual innovation.